Analyse du point de cristallisation dans la chronogenèse du processus de raccrochage - Anne Philipson; Pascal Dupont (Éducation et Socialisation)
Our study examines the impact of various temporalities - past, present, future - in the process of re-entry. Indeed, from the process to the realization of a professional project, temporality is at the heart of re-entry. We borrow from the linguist Gustave Guillaume (1924/1984), the term "chronogenesis" to designate the chronological organization of the process of re-entry. We will focus on crystallization point in this process, namely to the triggering factor of this return, in order to reveal that it serves as a starting point of the project.